Pengaruh Intellectual Capital Terhadap Kinerja Keuangan (Studi Empiris Perusahaan Manufaktur Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017-2020 - Intan Dwi Jufarlita Chryz Monica; Syarifah Ratih Kartika Sari; Djuwitawati Ratnaningtyas (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2021)
This study aims to examine Customer Capital, Human Capital and Structural Capital as components of Intellectual Capital on Financial Performance. Data obtained from secondary data from the annual reports of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2017-2020 period with a total of 10 companies. Data analysis was performed using multiple linear regression with SPSS version 16 for windows program.The results of this study indicate that thevariable Customer Capital has no significant effect on Financial Performance in Pharmaceutical Sub-Sector Companies for the 2017-2020 period. While thevariables Human Capital and Structural Capital have a significant effect on Financial Performance in Pharmaceutical Sub-Sector Companies for the 2017-2020 period. The F test shows that Customer Capital, Human Capital and Structural Capital Simultaneously Affect Financial Performance in Manufacturing Companies in the Pharmaceutical Sub-Sector Listed on the Indonesia Stock Exchange for the 2017-2020 Period.